Logotherapy For Mental Disorders A Literature Review - Setiyawan, Agus; Wardaningsih, Shanti (Jurnal Keperawatan Respati Yogyakarta, 2025)
Mental disorders will often have fatal consequences or decrease productivity in all aspects of a person's life. If mental disorders are not treated, they not only have an impact on the individual but also on the family, environment, and society and become a burden on a country. Actions are needed that can reduce mental disorders effectively, one of which is logotherapy. There are still few people who understand the positive impacts caused by this therapy, which actually provides many benefits. This study contributed to the effectiveness or influence of logotherapy on reducing mental disorders. This study used a literature review method using 3 databases: Pubmed, ScienceDirect, and Scopus. The article search obtained 8 articles that had previously been screened using PRISMA guidelines. This study looked for articles about the influence of logotherapy on mental disorders in general that were included in the inclusion criteria. The results of this study are There were 586 articles obtained from 4 databases, with 65 articles in the Pubmed database, 465 in the ScienceDirect database, and 60 in the Scopus database. A review of 8 articles showed that logotherapy could reduce symptoms of mental disorders such as emotional disorders, life expectancy, mental well-being, social well-being, level of hope, self-stigma, depression, suicidal ideation, hopelessness, anxiety, stress, and general health. Logotherapy can be applied to someone who experiences mental disorders. This therapy is a holistic therapy that can overcome mental disorders.